2023
DOI: 10.3390/su151411368
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development of Water Housing Using the Example of Poland: An Analysis of Scenarios

Abstract: At the turn of the 20th and 21st centuries, Polish cities began the process of returning to live by water. There is a growing interest in water reservoirs not only as places for recreation, but also as new areas suitable for living, at the very center of the city. Unfortunately, due to the lack of appropriate legal regulations, the dynamic development of floating homes (FHs) is starting to raise increasing concerns in Poland. Regardless of the potential direction of development in water construction in Poland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In the presented research, individual factors were identified at an earlier stage, when developing scenarios for the future development of FHs in Poland using the SSSs method. The research was presented in publications: [21,[23][24]. The determinants were selected based on a literature review, survey, interview and own observations.…”
Section: Input Data For Developing the Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…In the presented research, individual factors were identified at an earlier stage, when developing scenarios for the future development of FHs in Poland using the SSSs method. The research was presented in publications: [21,[23][24]. The determinants were selected based on a literature review, survey, interview and own observations.…”
Section: Input Data For Developing the Strategymentioning
confidence: 99%
“…Development strategies should include solutions to formal and legal [1][2][3][4][5][6][7][8][9], technical [5,[10][11][12][13][14], economic [1-3, 5, 7-8], environmental [15][16][17][18][19][20][21][22][23][24], demographic and socio-cultural [2,[25][26] issues.…”
Section: Introductionmentioning
confidence: 99%